Housebound versus nonhousebound patients with myalgic encephalomyelitis and chronic fatigue syndrome. (December 2016) - Pendergrast, Tricia; Brown, Abigail; Sunnquist, Madison; Jantke, Rachel; Newton, Julia L; Strand, Elin Bolle; Jason, Leonard A
Objectives: The objective of this study was to examine individuals with myalgic encephalomyelitis and chronic fatigue syndrome who are confined to their homes due to severe symptomatology. The existing literature fails to address differences between this group, and less severe, nonhousebound patient populations. Methods: Participants completed the DePaul Symptom Questionnaire, a measure of myalgic encephalomyelitis and chronic fatigue syndrome symptomology, and the SF-36, a measure of health impact on physical/mental functioning. ANOVAs and, where appropriate, MANCOVAS were used to compare housebound and nonhousebound patients with myalgic encephalomyelitis and chronic fatigue syndrome across areas of functioning, symptomatology, and illness onset characteristics. Results: Findings indicated that the housebound group represented one quarter of the sample, and were significantly more impaired with regards to physical functioning, bodily pain, vitality, social functioning, fatigue, postexertional malaise, sleep, pain, neurocognitive, autonomic, neuroendocrine, and immune functioning compared to individuals who were not housebound. Discussion: Findings indicated that housebound patients have more impairment on functional and symptom outcomes compared to those who were not housebound. Understanding the differences between housebound and not housebound groups holds implications for physicians and researchers as they develop interventions intended for patients who are most severely affected by this chronic illness.